Film-study as a source of formation of creative cross-cultural skills in multicultural context - Starostova, Liudmila; Piskunova, Larisa (Creativity Studies, 2016)
The authors propose to look at the cinema in the education process in terms of its potential use as a tool of formation of creative cross-cultural competence. Nowadays cinema is not just a synthetic art, it is deeply integrated into the basic structure of modern culture, and forms means capable of becoming an effective source of educational innovations. The article proposes the concept of film-study as a reference for the complex of methodical use of cinema in education. Analysis of different cases of inclusion of cinema in practical lessons allowed the authors to substantiate the connection of film-study method with the formation of students’ creative cross-cultural skills. As stated in the article, techniques of film-study method used by the authors contribute to the development of students’ cross-cultural competence relevant in a multicultural context of their professional and daily activities.